XYZ Corporation: utilizing Risk Solver Platform to improve soybean crushing profitability - Ceratti, Geovano (Kansas State University, 2018)
The growing number of participants in the grain market shows just how globalized this sector is in Brazil nowadays. It is difficult to distinguish between mergers and acquisitions of local companies and that of investment funds, which are actively engaged in acquiring a part or even the totality of Brazilian companies. For instance, the soybean crushing company “XYZ” that acquired some assets such as crushing plants in the state of Mato Grosso, located on the center-west region of Brazil and access to two port terminals to export the byproducts. This thesis contains data from January of 2014 to September of 2017, which includes prices of soybean and by products, freight rates, basis at the ports and operational costs. This information is from different sources including government and private agencies and Thomson Reuters Eikon software. This information was used to build a model in Microsoft Excel and by using the Risk Solver Platform, a statistic calculator tool and to find a solution to improve “XYZ” profitability. The results of the model suggest changes in the origination of grains, a reduction of the volume in some locations and increasing the volume originated in other locations. After running two different scenarios, “XYZ” profit increased by 3.81 million of Brazilian Reais.
Keywords: Soybeans; Optimization; Grain origination